A Review of Translational Animal Models for Knee Osteoarthritis. (27th December 2012) - Gregory, Martin H.; Capito, Nicholas; Kuroki, Keiichi; Stoker, Aaron M.; Cook, James L.; Sherman, Seth L.
Abstract : Knee osteoarthritis remains a tremendous public health concern, both in terms of health-related quality of life and financial burden of disease. Translational research is a critical step towards understanding and mitigating the long-term effects of this disease process. Animal models provide practical and clinically relevant ways to study both the natural history and response to treatment of knee osteoarthritis. Many factors including size, cost, and method of inducing osteoarthritis are important considerations for choosing an appropriate animal model. Smaller animals are useful because of their ease of use and cost, while larger animals are advantageous because of their anatomical similarity to humans. This evidence-based review will compare and contrast several different animal models for knee osteoarthritis. Our goal is to inform the clinician about current research models, in order to facilitate the transfer of knowledge from the "bench" to the "bedside."